Peran Media Sosial Sebagai Ekosistem Mikro dalam Mendukung Platform E-Learning Berbasis Komunitas: Kajian Literatur Sistematis - Abigail Virginia Christianti; Christianti , Abigail Virginia; Salsabila, Allysha Khansa; Savara, Intan ditya Putri (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The integration of social media into digital education has transformed how communities engage in collaborative learning. While social media platforms were initially designed for communication, they have evolved into micro-ecosystems that support community-based e-learning. This study conducts a Systematic Literature Review (SLR) to examine the role of social media as a micro-ecosystem in enhancing collaborative learning environments. Using the PRISMA protocol, 450 articles were initially identified from Scopus, Web of Science, IEEE Xplore, and Google Scholar. After multiple screening stages, 80 articles met the inclusion criteria and were analyzed in-depth. The findings indicate that platforms such as WhatsApp, Facebook, YouTube, and Edmodo significantly enhance learning engagement, collaboration, and knowledge sharing. Specifically, student engagement increased by up to 40% compared to traditional LMS-based methods, with satisfaction rates exceeding 80% among Edmodo users. Moreover, WhatsApp communities achieved a message open rate of 98%, demonstrating high responsiveness and interaction quality. However, challenges such as low digital literacy, data privacy concerns, and distractions from non-academic content were also identified. This research contributes a comprehensive synthesis of how social media can function as a micro-ecosystem to foster inclusive, flexible, and community-driven learning. It also offers strategic recommendations for educators and policymakers to optimize the use of social platforms for education in the digital era.